2010
DOI: 10.1007/s00248-010-9785-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Relative Humidity on Deinococcus radiodurans’ Resistance to Prolonged Desiccation, Heat, Ionizing, Germicidal, and Environmentally Relevant UV Radiation

Abstract: To test the effect of humidity on the radiation resistance of Deinococcus radiodurans, air-dried cells were irradiated with germicidal 254 nm UV, and simulated environmental UV or γ-radiation and survival was compared to cells in suspension. It was observed that desiccated cells exhibited higher levels of resistance than cells in suspension toward UV or γ-radiation as well as after 85°C heat shock. It was also shown that low relative humidity improves survival during long-term storage of desiccated D. radiodur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 49 publications
3
54
2
1
Order By: Relevance
“…Members of the genus Deinococcus are known to exhibit high resistance to UV and gamma radiation, owing to their red or yellow pigments and their ability to repair damaged DNA (Asker et al, 2008). Air-dried Deinococcus cells have exhibited higher resistance to environmental stressors than normal cells (Bauermeister et al, 2011). Accordingly, Deinococcus species have often been detected in extreme environments such as high-altitude atmospheric areas as dominant species.…”
Section: Ubiquitous Bacteria Detected In Extreme Environmentsmentioning
confidence: 99%
“…Members of the genus Deinococcus are known to exhibit high resistance to UV and gamma radiation, owing to their red or yellow pigments and their ability to repair damaged DNA (Asker et al, 2008). Air-dried Deinococcus cells have exhibited higher resistance to environmental stressors than normal cells (Bauermeister et al, 2011). Accordingly, Deinococcus species have often been detected in extreme environments such as high-altitude atmospheric areas as dominant species.…”
Section: Ubiquitous Bacteria Detected In Extreme Environmentsmentioning
confidence: 99%
“…One of the most studied extremophiles, Deinococcus radiodurans, is a Gram-positive bacterium possessing extremely high tolerances to radiation, desiccation, and other environmental stresses; these attributes have sparked significant interest in this organism for applications in bioremediation and metal detoxification (19)(20)(21). Indeed, D. radiodurans has been engineered for use in radioactive waste manipulation through incorporation of heterologous genes for toluene degradation and mercury and uranium reduction, demonstrating the ability for simultaneous reduction of multiple wastes (22,23).…”
mentioning
confidence: 99%
“…Protection and repair mechanisms guarantee the survival of dried Chroococcidiopsis when experiencing additional environmental stressors [32,33]. The major effect caused by space vacuum is desiccation, while concerning solar and galactic cosmic radiation, desiccation-tolerant organisms exhibit a resistance towards UV and ionizing radiation; evidences suggested that such a resistance might be enhanced when cells are irradiated in the dried status, as reported for Deinococcus radiodurans [34].…”
Section: Desert Cyanobacteria and The Terrestrial Analogues Of Marsmentioning
confidence: 91%